Direct Instruction with SAVI Learning Model to Improve Students’ Mathematical Problem-Solving Ability: A Descriptive Study - Salingkat, Suhartini; Nihayah, Elok Faik Khotun (FKIP Universitas Lampung, 2022)
This research aims to describe the ability to solve the problems of students’ mathematics and through direct learners based on SAVI is expected to provide a change in the ability to solve problems of students class VII in Junior High School 6 Bualemo, especially on triangular material. This type of research is descriptive with a qualitative approach. The subjects in this study were two class VII students. The results of this study showed that students' math problem-solving abilities were still in the